VERY LONG-CHAIN ACYL-COA DEHYDROGENASE DEFICIENCY IN A CHILD (EuroMediterranean Biomedical Journal, 2026)
This report concerns a patient affected by Very Long-Chain Acyl-CoA Dehydrogenase (VLCAD) deficiency, a rare inherited metabolic disease with different severity levels that can arise at all ages. VLCAD is involved in metabolic pathway of p-oxidation regarding energy production during prolonged fast.A 18-months old boy experienced a febrile crisis, during which a severe hypoketotic hypoglycaemia emerged, leading him to a multi organ failure that ultimately caused death.Immediate administration of a therapy, even during diagnostic phase, is crucial in this kind of metabolic inherited diseases.